The virulome of Streptomyces scabiei in response to cello-oligosaccharide elicitors. Issue 1 (17th January 2022) - Deflandre, Benoit; Stulanovic, Nudzejma; Planckaert, Sören; Anderssen, Sinaeda; Bonometti, Beatrice; Karim, Latifa; Coppieters, Wouter; Devreese, Bart; Rigali, Sébastien
Abstract : The development of spots or lesions symptomatic of common scab on root and tuber crops is caused by few pathogenic Streptomyces with Streptomyces scabiei 87–22 as the model species. Thaxtomin phytotoxins are the primary virulence determinants, mainly acting by impairing cellulose synthesis, and their production in S. scabiei is in turn boosted by cello-oligosaccharides released from host plants. In this work we aimed to determine which molecules and which biosynthetic gene clusters (BGCs) of the specialized metabolism of S. scabiei 87–22 show a production and/or a transcriptional response to cello-oligosaccharides. Comparative metabolomic analyses revealed that molecules of the virulome of S. scabiei induced by cellobiose and cellotriose include (i) thaxtomin and concanamycin phytotoxins, (ii) desferrioxamines, scabichelin and turgichelin siderophores in order to acquire iron essential for housekeeping functions, (iii) ectoine for protection against osmotic shock once inside the host, and (iv) bottromycin and concanamycin antimicrobials possibly to prevent other microorganisms from colonizing the same niche. Importantly, both cello-oligosaccharides reduced the production of the spore germination inhibitors germicidins thereby giving the 'green light' to escape dormancy and trigger the onset of the pathogenic lifestyle. For most metabolites - either with induced or reduced production - cellotriose was revealed to be a slightly stronger elicitor compared to cellobiose, supporting an earlier hypothesis which suggested the trisaccharide was the real trigger for virulence released from the plant cell wall through the action of thaxtomins. Interestingly, except for thaxtomins, none of these BGCs' expression seems to be under direct control of the cellulose utilization repressor CebR suggesting the existence of a yet unknown mechanism for switching on the virulome. Finally, a transcriptomic analysis revealed nine additional cryptic BGCs that have their expression awakened by cello-oligosaccharides, suggesting that other and yet to be discovered metabolites could be part of the virulome of S. scabiei .